Weakest bus frequency identification of power system via TFDI - Al Mentefik, Athraa Iessa Shaaban; Abdul Wahab, Noor Izzri; Mariun, Norman (Universiti Putra Malaysia Press, 2017)
One of the concerns in power system preventive control and security assessment is to find the point where the voltage and frequency collapse and when the system forces a severe disturbance. Identifying the weakest bus in a power system is an essential aspect of planning, optimising and post-event analysing procedures. This paper proposes an approach to identify the weakest bus from the frequency security viewpoint. The transient frequency deviation index for the individual buses is used as the weakest bus identification as well as a frequency security indicator. This approach will help to determine the bus with the worst deviation, which helps to analyse the system disturbance, takes proper control action to prevent frequency failure, and most importantly, observes consumer frequency. The approach is applied to the WSCC 9 bus test system to show the feasibility of the method.